Business Environment and Strengthening of the Economy: Selected Countries of Western Asia - Amiri, Hossein; Barani, Masoumeh Beiranvand (Economy of Regions, 2020)
The business environment is one of the factors that affect the performance and growth of firms. The business environment is a set of conditions that affect the state of the economy. This paper examines how improvement of the business environment influences strengthening of the economy in the selected countries of western Asia (23 countries) by using panel data method for the period from 2010 to 2017. In other words, we hypothesise that the business environment positively and significantly affects strengthening of the economy in these countries. The paper aims to examine the explanatory variables of strengthening of the economy. The dependent variable is the sum of budget deficit and the facilities of financial and credit institutions to the state budget minus the tax revenue to the state budget. The independent variables are business index, good governance index, economic misery index, foreign direct investment, gross fixed capital formation, government expenditures and population growth. The research findings indicate that the business environment has a positive and significant impact on strengthening of the economy. Thus, in order to strengthen the economy in the considered countries, we suggest using some approaches facilitating the business environment, particularly for productive sectors of the economy, focused on generating productive employment.